Foreign Aid and Tourism Induced Electricity Consumption in the Turkish Republic of Northern Cyprus - Wolde-Rufael, Yemane; Mulat-Weldemeskel, Eyob (Energy Economics Letters, 2022)
The aim of this paper is to investigate the role of foreign aid and tourism in inducing electricity consumption in a tourism and a foreign aid dependent Turkish Republic of Northern Cyprus (TRNC) for the period 1977-2017. Applying the Autoregressive Distributive Lag (ARDL) approach to cointegration, we found that both foreign aid and tourism positively and significantly induce electricity consumption. Our results are robust to the Canonical Cointegrating Regression (CCR), the fully modified ordinary least squares (FMOLS) and the dynamic ordinary least squares (DOLS) long-run tests. We also found bidirectional causality between foreign aid and electricity consumption while unidirectional causality from tourism to electricity consumption. Both foreign aid and tourism induce electricity consumption indicating that they are both important sources of the growth of electricity consumption. However, since energy consumption is the main source of environmental degradation, the TRNC should develop an energy strategy that promotes environmental sustainability.